PENDAMPINGAN DI YAYASAN PENDIDIKAN ISLAM JIWANALA DALAM RANGKA KEGIATAN PROMOSI DAN PAMERAN - Sadana Devica (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
Mentoring at the Jiwanala Islamic Education Foundation is a form of community service activity carried out by Ubaya Polytechnic lecturers. This activity is carried out to provide insight to the marketing team at educational foundations to be able to optimize marketing activities by participating in educational exhibitions and conducting sales promotions. Assistance was provided starting from finding information about organizing educational exhibitions, designing, and making a booth, as well as preparing promotional media to be used during the exhibition. With this assistance, the marketing team of the Jiwanala Islamic Education Foundation can prepare marketing tools so that they can reach the right target market.